Legal Regulation of the Role of Artificial Intelligence in Detecting Personal Financial Data Violations in the Saudi Legal System: A Descriptive Analytical Study - Reema Jaser Al-Juwaiser (International Journal of Law Research and Studies, 2025)
This study examines the legal framework governing the role of artificial intelligence (AI) in detecting personal financial data violations within the Saudi legal system, focusing on the technological and legal challenges in this domain. The research highlights the importance of AI as an advanced tool for analyzing large datasets and identifying suspicious patterns indicative of violations or financial crimes. It demonstrates how AI applications can enhance the accuracy and efficiency of financial oversight systems while safeguarding individuals’ rights and privacy. However, the growing reliance on these technologies raises questions about the compatibility of existing legislation with technological advancements. The study reviews Saudi legislation, such as the Personal Data Protection Law and the Anti-Cybercrime Law, analyzing their adequacy to ensure the safe and effective use of AI in this area. It highlights potential gaps in the current legal framework, such as the lack of clear regulatory guidelines on big data usage and the need for a balanced approach between privacy protection and technological benefits. The research also compares the Saudi system to international experiences, such as the European GDPR and California’s CCPA, offering a comprehensive perspective on improving Saudi legal regulations. The study emphasizes the need for a progressive and flexible legal framework capable of accommodating rapid developments in AI. It underscores the importance of enhancing transparency in data collection and analysis while establishing stringent controls to regulate AI use, ensuring a balance between individual rights protection and technological progress. The research provides recommendations for advancing Saudi legislation by adopting international standards and implementing more efficient oversight mechanisms. In conclusion, the study calls for collaboration among regulatory and technical entities to promote the safe use of AI in detecting financial data violations. It highlights the importance of raising public awareness about individual rights in data protection while fostering technological innovation to support Saudi Arabia’s economic and social sustainability goals.